Where Does the Minimum Wage Bite Hardest in California? - William E. Even; David A. Macpherson (Institute of Labor Economics (IZA), 2018)
This study uses employment data on California county-industry pairs (CIPs) between 1990 and 2016 to test whether minimum wage increases caused employment growth to slow most in the CIPS with a large share of low wage workers. Evidence supports the hypothesis, and we use the estimates to simulate the effect of a 10 percent increase in the minimum wage. The simulations suggest that a 10 percent increase could cause a 3.4 percent employment loss in the average CIP in California. The job loss is projected to be concentrated in two industries: accommodation and food services, and retail. While the most populated counties of California are expected to incur the largest employment loss in terms of the number of workers, the smaller counties generally experience a larger percentage point loss in employment due to the lower wages and the greater number of workers that would be affected by the minimum wage hike. Moreover, there is substantial variation across counties in terms of the percentage of jobs lost within a given industry.
Keywords: J23; J30; J38; 330; labor demand; California; employment; minimum wage